Constructing the Uzbek state : narratives of post-Soviet years - Laruelle, Marlène (Contemporary Central Asia (Lanham, Md.), 2017)
This collection provides a broad examination of contemporary Uzbekistan. The contributors analyze its geostrategic significance, its economic potential, and its demographic importance. This study also argues that the country's political, social, and cultural evolutions symbolize the transformations of the region as a whole.